UJI EFEK EKSTRAK UMBI BAWANG PUTIH (ALLIUM SATIVUM L.) TERHADAP KADAR GLUKOSA DARAH TIKUS WISTAR (RATTUS NORVEGICUS) YANG DIINDUKSI ALOKSAN - Cahya, Bimbi Putri; Mambo, Christi; Wowor, Mona P. (Universitas Sam Ratulangi, 2015)
Abstract: Garlic (A. sativumL.) is one of many herbal medicine that have been used worldwide to prevent and treat a lot of disease, for example to treat diabetes mellitus. This research aimed to evaluate the effect of garlic bulbs extract administration on elevated blood glucose levels on Wistar rats (R. norvegicus) induced by alloxan. The subjects inthis research were male Wistar rats with total of 18 samples divided into six groups as follows negative control group and five hyperglycemic groups induced by 130 mg/kgBW of alloxan. Garlic bulbs extract was administered with dose of 3 mg/200 gBW of rat, 6 mg/200 gBW of rats, and 12 mg/200 gBW on each groups of hyperglycemic rats, insulin analogue was administered on positive control groups of hyperglycemic rats, and only alloxan was given to the last group. Blood glucose levels was measured on day zero, day one and day two every six hours on 0, 6, 12, 18, and 24. Data from the measurement showed that 6 mg/200 gBW and 12 mg/200 gBW of garlic bulbs extract can reduce elevated blood glucose levels on Wistar rats. Garlic bulbs extract has shown effect on reducing elevated blood glucose levels on Wistar rats induced by alloxan.Keywords: Allium sativum L., Garlic Bulbs, Blood Glucose Levels, AlloxanAbstrak: Bawang putih (A. Sativum L.) diyakini masyarakat sebagai salah satu tanaman obat yang mampu mencegah dan mengobati berbagai penyakit, salah satunya diabetes. Penelitian ini bertujuan untuk menguji apakah pemberian ekstrak umbi bawang putih dapat menurunkan kadar glukosa darah tikus Wistar (R. norvegicus) yang diinduksi aloksan. Subjek penelitian berupa tikus Wistar jantan berjumlah 18 ekor yang dibagi dalam 6 kelompok, terdiri atas satu kelompok kontrol negatif dan lima kelompok tikus Wistar yang diberi aloksan dengan dosis 130 mg/kgBB yang menyebabkan tikus Wistar dalam keadaan hiperglikemik. Tikus hiperglikemik diberi ekstrak umbi bawang putih dengan dosis 3 mg/200 gBB tikus, 6 mg/200 gBB tikus, dan 12 mg/200 gBB tikus, kelompok kontrol positif diberi analog insulin, dan satu kelompok hanya diberi aloksan. Data diperoleh dari pemeriksaan kadar glukosa darah pada semua kelompok tikus Wistar pada hari ke nol, pertama, dan kedua pada jam ke-0, 6, 12, 18, dan 24. Hasil penelitian menunjukkan bahwa pemberian ekstrak umbi bawang putih dengan dosis 6 mg/200 gBB tikus dan 12 mg/200 gBB tikus mempunyai efek menurunkan kadar glukosa darah tikus Wistar.Kata kunci: Allium sativum L., Umbi Bawang Putih, Kadar Glukosa Darah, Aloksan